Anti-Cancer Potential of Vateria Indica L. Stem Bark Enriched Fractions in EAC and C6 Cell lines-an In-Vitro Study - Richard Lobo (Journal of Global Pharma Technology, 2017)
The western Ghats of India present Pharmacognosists and botanist a rich source of biological diversity to explore their unearthed potential. V. indica, one among the thousands of such plant growing in the southern states of India especially in Kerala, Karnataka and Tamil Nadu, at about 750 m altitude is a slow growing plant of Dipterocarpaceae family. The present study was aimed to investigate the anticancer potential of stem bark of Vateria indica by trypan blue exclusion method and Sulphorhodamine B assay against C6 and EAC cell lines respectively. From the studies it was found that the acetone fraction of V. indica demonstrated high activity whereas ethanolic and petroleum fraction were moderately active against C6 cell lines respectively. It was also observed that the ethanolic and ethyl acetate fraction of V. indica were highly active whereas petroleum ether extract was moderately active against EAC cell lines.Keywords: Vateria indica, Anticancer potential, SRB assay.